Knowledge and Skills of Mothers/Care Givers of Children Under Five Years in Communities with Home Based Management of Malaria in Tamale, Northern Region, Ghana, 2013 - Mukaila Z. Mumuni; Mohammed A. Soghaier; Korkortiakor Baba S. Zankawah; Bukari Musah; Cynthia Kubio; Tanko Mahamadu; Assau Goodstaff (AIMS Press, 2016)
Background: Malaria is still one of the major public health problems. More than 400 million cases of malaria are reported each year worldwide, Sub-Saharan Africa is the most affected region where about 90% of all malaria deaths in the world occur especially in children under five years of age. Home based management of Malaria showed a tremendous effect on reducing mortalities among children in Ghana. Objectives: to determine the current level of knowledge and skills of mothers in Tamale Metropolitan Area in the northern region of Ghana in terms of disease identification, management and transmission of malaria. Methodology: A cross sectional study conducted in 2013 involved 400 families and mothers/care givers with children less than five years were selected randomly and represented urban, peri-urbanand rural settings. Results: More than 90% of respondents identified malaria by presence of fever while 57.5% used fever as a cardinal sign. 91% of participants sought early treatment in urban and peri-urban settings while 85% did so in rural sites. 55% of participants administered the correct doses daily but only 17% of them knew the side effects of Antimalarial medications used. Almost all participants were aware about transmission of malaria, when to repeat the drug dose and usage of paracetamol as a medicine to reduce body temperature. Conclusion: The overall knowledge and skills demonstrated are encouraging, there is no much difference between urban and rural settings. Community based initiatives should be strengthened and promoted to provide homemade solutions to saving lives and resources.